End of story : a novel [compact disc, unabridged] - Finn, A. J. (HarperCollins, 2024)
Sebastian Trapp, a reclusive mystery novelist, only has months to live. Twenty years earlier, Sebastian's first wife and teenaged son vanished, never to be seen again. Trapp invites Nicky Hunter to his spectacular San Francisco mansion to help draft his life story. Nicky becomes obsessed with finding the truth. Did the perfect crime writer commit the perfect crime?